Introduction to the thematic issue: transformative relationships between tourism and technology - Liasidou, Sotiroula; Pipyros, Kosmas (My University, 2025)
Purpose The article offers a thorough and insightful examination of the transformative role technology plays in the tourism industry by introducing the articles of the thematic issue. Design/methodology/approach The discussion approach involves reviewing relevant literature and providing a detailed description of each article in the thematic issue. In particular, the issue consists of a compilation that includes a series of research articles, case studies and theoretical discussions; quantitative and qualitative research enquiries that examine various aspects of tourism technology, such as cybersecurity, digital marketing, smart tourism initiatives, the role of social media and the impact of emerging technologies like artificial intelligence through different perspectives of discussion. Findings Each article provides useful conclusions that shed light on the various ways that technologies can transform and revolutionize the tourism industry. Technology and tourism have a reciprocal relationship, where technology not only transforms tourism but also shapes it. Originality/value This thematic issue contributes and provides new insights into the evolving dynamics of tourism and technology, offering a multidisciplinary perspective that bridges theoretical frameworks and practical applications for industry stakeholders.
Keywords: Cybersecurity; Revenue management; Tourism; Technology; Digital marketing; Smart tourism; Consumer behavior; Artificial intelligence; Internet of Things; Sustainable tourism